2019
DOI: 10.4103/aer.aer_104_19
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone versus hyaluronidase as an adjuvant to local anesthetics in the ultrasound-guided hydrodissection of the median nerve for the treatment of carpal tunnel syndrome patients

Abstract: Background:Carpal tunnel syndrome (CTS) is one of the most common focal entrapment neuropathies. Although the exact etiology remains unclear, high-pressure-related intracarpal tunnel compression of the median nerve (MN), progressing ischemia, and mechanical strangulation are common mechanisms. The therapeutic managements for CTS depend on the disease severity, varying from a conservative treatment to surgical interventions. Conservative treatment is helpful for most of the patients with mild-to-moderate CTS. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 25 publications
(31 reference statements)
0
45
0
Order By: Relevance
“…Last, the present study was not the first study to evaluate the CSA and mobility of the median nerve after steroid injection 22,23 . However, the two studies reported previously followed a different protocol to evaluate the same outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Last, the present study was not the first study to evaluate the CSA and mobility of the median nerve after steroid injection 22,23 . However, the two studies reported previously followed a different protocol to evaluate the same outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Although the effect of dextrose, conducted by a previous RCT, lasted for up to 6 months (Wu et al, 2017b), the effect of perineural saline injection showed an improved BCTQ only until the 3rd month post-injection which deteriorated by the 6th month of follow-up (Wu et al, 2019). Similarly, another RCT reported the improvement of BCTQ did not last until the 6th month after hydrodissection (with either steroid or hyaluronidase) (Alsaeid, 2019). In this study, via post-hoc Bonferroni analysis, pain and functional outcomes were not significant between the 3rd and 6th months follow-up in the 1, 2 and 4-ml groups (VAS: p 1.000, 0.895, 0.750, respectively; BCTQ: p 1.000, 1.000, 0.295, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…The flow chart in Figure 1 presents the results describing the exclusions at different stages during the review process. Ten studies were included in this systematic review ( van Veen et al, 2015 ; Wu et al, 2017a ; Wu et al, 2017b ; Malahias et al, 2018 ; Roghani et al, 2018 ; Wu et al, 2018 ; Alsaeid, 2019 ; Güven et al, 2019 ; Senna et al, 2019 ; Shen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…When comparing one injectate to another, D5W, PRP, and hyaluronidase gave greater improvement than their steroids counterparts (Wu et al, 2018;Alsaeid, 2019;Senna et al, 2019). Regarding main electrodiagnostic parameters (SNCV and DML) findings, D5W and hyaluronidase resulted in superior outcomes comparing to NSS and dexamethasone, respectively (Wu et al, 2017b;Alsaeid, 2019). PRP plus splinting also significantly improved main electrodiagnostic parameters (Güven et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation